Evaluación del proceso de reclutamiento y selección del personal en la Empresa Pública de Santo Domingo EP- CONST, 2020 - Freire Loor, Cristian Joel (2022)
The present investigative work had the purpose of evaluating the process of recruitment and selection of personnel in the Public Construction, Housing and Cleaning Company of Santo Domingo EP-CONST. The methodology applied was field, bibliographic, deductive, inductive and analytical, the research techniques were applied through interviews and observation, likewise, for the process techniques the AS IS diagram, process sheet, value analysis and added and time were used. The management of the investigation was applied in three phases: representation, evaluation and proposal to improve the process of recruitment and selection of company personnel. From the results obtained, it was evidenced that the staff does not have constant training to carry out the hiring processes efficiently, which was corroborated by the poor results obtained in the evaluation of the process. The improvement plan focused on regulatory processes, performance and potential, in order to improve and optimize the hiring of personnel in the company. Therefore, it is concluded that the training and socialization of the personnel of the Human Talent Unit allow the optimization of human and financial resources.